Practicing Components of Women Empowerment and Youth Perception: A Study Conducted at PMAS Arid Agriculture University Rawalpindi - Saman, Faiqa; Chaudhary, Abid Ghafoor (Annals of Human and Social Sciences, 2023)
The paper under discussion deals with youth perception about women empowerment. The objective of study was to draw a link between women empowerment and educational attainment. The conducted study based upon hypothesis that educated youth have positive attitude towards practicing the components of women empowerment. The study selected Pir Mehar Ali Shah Arid Agriculture University Rawalpindi as research locale. Researcher has chosen explanatory methodology for administering the research with its respective goals. The target population includes students of PMAS AAUR. A sample of about 286 students was drawn by simple random sampling technique. The data sourced through subjects of study proved hypothesis of the study true. The key findings revealed that youth perception is constantly changing in respect to the conception of women empowerment and affirmed education is playing key role in this regards. The researcher has also put forth the significant finding that the educated youth of a country with minor exception is in favor of providing women’s with their basic rights such as education, health, freedom of movement, job participation, decision making, property rights, political rights and also women’s right of spouse selection. Moreover, research study portrays that a positive change in upcoming generations regarding providing women their rights is one the characteristic way to empower them. The future implications of the study suggest invitation for the researchers to explore more about such anthropogenic practices that could support the youth through empowering the women in society.